Development of Computer Based Test Instrument for Higher Order Thinking Skills (CBT-HOTS) on Chemical Bonding Materials - Sulistiani Sulistiani; Muhammad Yusuf (Chemistry Education Department, 2022)
This study aimed to produce a computer-based test instrument for higher-order thinking skills (CBT-HOTS) on the chemical bonding materials and to determine the higher-order thinking skills of students in Class X MIA at MAN Binjai Academic Year 2021/2022. This research employed the ADDIE model of Research and Development (RD). The test instrument was created in the form of multiple-choice consisting of 30 questions measuring the cognitive domains of analyzing (C4), evaluating (C5), and creating (C6). Based on the findings, the developed instrument was declared feasible for use, considering that it had met the required content validity by expert assessments using the Aiken’s V index in the range of 0.97 to 1.00 and the reliability value of 0.93. The students' higher-order thinking skills on chemical bonding materials were included in the